2D lead-free organic–inorganic hybrid exhibiting dielectric and structural phase transition at higher temperatures. Issue 24 (6th June 2022) - Shao, Ting; Gong, Jun Miao; Liu, Jia; Han, Li Jun; Chen, Ming; Jia, Qiangqiang; Fu, Da Wei; Lu, Hai-Feng
Abstract : A novel switchable molecular dielectric material [3-3-difluorocyclobutylammonium]2 CdCl4 was synthesized. It shows a reversible phase transition at 353.95 K and rapid switching and reversibility between high and low dielectric states for several cycles. Abstract : 2D organic–inorganic hybrids have unique features, such as structural tunability and stability, thus they have received tremendous scientific attention in recent years. Here, we report a novel switchable molecular dielectric material [3-3-difluorocyclobutylammonium]2 CdCl4 (compound 1 ) that undergoes a reversible phase transition at 353.9 K. The apparent temperature-dependent dielectric behavior of compound 1 was observed. Besides, the dielectric phase change shows rapid switching and reversibility between high and low dielectric states for several cycles, which confirms its superior dielectric stability. These properties make it a potential candidate for switchable dielectric materials.